Network pharmacology, bioinformatics and in vitro/in vivo validation elucidate the anti-lung cancer activities and potential targets of Rhoifolin - Qian, Jing; Cheng, Wei; Li, Shuangyan; Deng, Li; Gao, Di; Zhang, Xue; Zhang, Yunhui (Frontiers in Pharmacology, 2026)
BackgroundRhoifolin (ROF), a naturally occurring flavonoid, exhibits broad bioactivities, but its therapeutic potential and underlying mechanisms in lung cancer remain largely unknown. This study was designed to systematically investigate the anti-tumor effects of ROF and identify its key molecular targets.Materials and methodsAnti-tumor activities of ROF were assessed using CCK-8, colony formation, flow cytometry, wound healing, and Transwell assays, respectively. An integrated approach combining network pharmacology, transcriptomic analysis with machine learning was employed to identify primary targets. The Kaplan-Meier survival and ROC curve analyses also evaluated the targets’ clinical outcomes and tumor microenvironment through the Cancer Genome Atlas (TCGA) data and single-cell RNA sequencing. The confirmed experimentally via RT-qPCR, Western blot, and immunofluorescence. The drug-target interaction was characterized by molecular docking and dynamics simulations. Finally, the in vivo antitumor efficacy and the safety of ROF were assessed in an H358 xenograft mouse model.ResultsROF potently inhibited lung cancer cell proliferation (IC50: 15.35–33.84 µM), migration, and invasion, while inducing G2/M phase arrest and apoptosis (increased Bax/Bcl-2 ratio). ROF also impaired metastatic potential as evidenced by upregulated E-cadherin and downregulated N-cadherin in vitro. EPHB2 was identified as the most therapeutically relevant, showing high diagnostic value (AUC=0.856) and a significant correlation with poor patient survival. The experimental validation confirmed that ROF downregulates EPHB2 expression at both the mRNA and protein levels in a dose-dependent manner. Molecular docking and dynamics simulations predicted a stable, high-affinity interaction between ROF and the EPHB2 protein. Importantly, ROF treatment significantly suppressed tumor growth in vivo without discernible toxicity.ConclusionRhoifolin exerts potent and selective anti-lung cancer activity by directly targeting and downregulating EPHB2, providing a strong rationale for its further development as a novel therapeutic agent for lung cancer.